2017
DOI: 10.1111/jocn.13931
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an effective nursing clinical instructor: The state of the science

Abstract: Aims and objectives: To analyse the perceived characteristics of an effective nursing clinical instructor and methods for measure instructor effectiveness. This review also examined importance of characteristics based on student age. Background:The clinical instructor has a vital role in clinical education. While the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 34 publications
1
54
0
12
Order By: Relevance
“…In 2012, Allen et al published their research in nursing education examining the relationship between EI ability and the effectiveness of clinical instructors 17 . They measured EI and CTE using the Emotional Quotient Inventory: Short (EQ‐i:S) 8 and the NCTEI 10 . Allen et al's study found that higher EI scores were achieved by instructors who effectively communicated expectations to students and provided useful feedback.…”
mentioning
confidence: 99%
“…In 2012, Allen et al published their research in nursing education examining the relationship between EI ability and the effectiveness of clinical instructors 17 . They measured EI and CTE using the Emotional Quotient Inventory: Short (EQ‐i:S) 8 and the NCTEI 10 . Allen et al's study found that higher EI scores were achieved by instructors who effectively communicated expectations to students and provided useful feedback.…”
mentioning
confidence: 99%
“…of 10 Approachability was also highlighted by Jansson and Ene [31] as a positive attitude because of the security transmitted to placement students. This, together with interpersonal skills, are the two characteristics that a preceptor must have to be effective, according to the conclusions highlighted in a recent integrative review [32]. According to the study by Niederriter et al [33], both accessibility and availability of the clinical preceptor are important characteristics that enhance the learning experience, as they contribute to the establishment of a relationship of trust and a feeling of comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, clinical education was delivered via hospital-based bedside teaching and described as the experiential capstone to one's theoretical knowledge and research (Flexner, 1910;Rolleston, 1939). Often orchestrated by the preceptor, this apprenticeship model employed a passive, practical approach responsible for exposing learners to the "real-life" of the profession (Collier, 2017).…”
Section: Defining Clinical Educationmentioning
confidence: 99%